Using partial justice to interrogate the meanings and applications of social justice in service-learning - Mtawa, Ntimi N. (Critical Studies in Teaching and Learning, 2023)
This paper provides an account of the concept of social justice and how it is loosely and uncritically defined and applied in service-learning context. Social justice is deemed as an approach to service-learning, which allows all actors to actively participate in decision-making, share power and benefit equally. This framing of social justice in service-learning is largely within the realm of John Rawls’ perfect justice. There is relatively little attention given to small and actionable changes yielded in and through service-learning. As such, this paper uses the concept of ‘partial justice’ as purported by Amartya Sen to interrogate the meanings and applications of social justice in service-learning. The paper draws on qualitative data collected through document analysis, focus groups and semi-structured interviews with students, staff, and community members. The focus and contribution of the paper is timely and pertinent given the unexamined conceptions and use of social justice in service-learning context.